2019
DOI: 10.1007/s12111-019-09420-2
|View full text |Cite
|
Sign up to set email alerts
|

Black Intimacies Matter: the Role of Family Status, Gender, and Cumulative Risk on Relationship Quality Among Black Parents

Abstract: Studies show that married families report higher levels of relationship quality relative to unmarried families; yet, limited attention has been given to differences in relationship quality between married and unmarried Black families. The authors examined the interplay between family status, gender, and cumulative risk exposure on relationship quality among Black parents. The results suggest that (a) differences between married and unmarried parents only emerged on two measures of relationship quality, (b) mar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 35 publications
0
13
0
Order By: Relevance
“…As such, racial economic inequality reflects historical and contemporary forms of oppression and social exclusion via discriminatory processes. Racial economic inequities have far‐reaching implications for racial variations in relationship outcomes between intimate partners by accumulating and eroding a couple's ability to foster a healthy intimate union (Bryant et al, 2010 ; Williams et al, 2019 ), which, in turn, may lead to increased rates of dissolution (Pietromonaco & Overall, 2020 ). Such difficulties are likely to be exacerbated by the pandemic, as couples spend more confined time together (Boserup et al, 2020 ; Bradbury‐Jones & Isham, 2020 ).…”
Section: The Unequal Impact Of Covid‐19 Across Racialized Groupsmentioning
confidence: 99%
“…As such, racial economic inequality reflects historical and contemporary forms of oppression and social exclusion via discriminatory processes. Racial economic inequities have far‐reaching implications for racial variations in relationship outcomes between intimate partners by accumulating and eroding a couple's ability to foster a healthy intimate union (Bryant et al, 2010 ; Williams et al, 2019 ), which, in turn, may lead to increased rates of dissolution (Pietromonaco & Overall, 2020 ). Such difficulties are likely to be exacerbated by the pandemic, as couples spend more confined time together (Boserup et al, 2020 ; Bradbury‐Jones & Isham, 2020 ).…”
Section: The Unequal Impact Of Covid‐19 Across Racialized Groupsmentioning
confidence: 99%
“…First, for example, prior research has consistently shown that Black Americans, relative to other racialized groups, are less likely to be married (Raley et al, 2015;Raley & Sweeney, 2009), and more likely to experience a nonmarital childbirth (Wildsmith et al, 2018). Second, previous research shows that Black families, compared to White families, report lower levels of relationship quality between partners (Broman, 2005;Bulanda & Brown, 2007;Williams & Perry, 2019;Williams, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Other studies have more broadly examined increasing racial segregation and labor fragmentation at higher levels using ACS data, but they have not been able to look at the overlaps of such variables at a high spatial resolution (Lichter, Parisi, and Taquino 2012). Many studies have examined the evolving family complexity in the United States using ACS data at a national or state level (Bloome 2017; Maralani 2013), but these studies increasingly take a longitudinal perspective to examine evolving cohabitation patterns and socioeconomic implications, including racialized contours (Carlson and Corcoran 2001; Williams, Simon, and Cardwell 2019). Still, empirical research is needed on the geographic distribution of these patterns.…”
Section: Resultsmentioning
confidence: 99%